Analisis Struktur Bawah Jembatan 4 Kota Baru Parahyangan - Fadilah, Anisa; Roestaman, Roestaman (Jurnal Konstruksi, 2017)
In general, the bridge structure is divided into two parts, namely the upper structure and the bottom structure. The case study is only about the structure under abutments and pillars with the objective of obtaining the strength of the workload, the need for the pillar structure reinforcement, and the axial capacity of the foundation axial allowable. The method used is to conduct a literature study to perform a comparative analysis of the structural strength of the analytical results with the field. The dimensions reviewed have been qualified against the stability of boling ≥ 2.2 and the stability of shear ≥ 1,1. The carrying aloowable capacity of bored pile from each method is 801 tons,  218,93 tons, 678,24 tons on abutment and 803,72 tons, 227,47 tons, 678,24 tons on pillar, while in the field of 500 and 600 tons. For calculation of reinforced concrete reinforcement used is K 500 (fc '= 41,5 MPa) and K 300 (fc' = 24,9 MPa). Requirement of one pier wall got the whole of As 120000 mm2. The bending strength requirement of Asx pile cap is 4894 mm2, used reinforcement D32 - 150, Asy is 4320 mm2 used D32 - 150. The direction of x 2447 mm2 is used 25-21, the direction of y is 2160 mm2 with the D25 - 200 reinforcement. Shear reinforcement of x is used D13 - 350 reinforcement and y direction with D13 - 400 reinforcement.